Dung Beetles Reduce Clustering of Tropical Tree Seedlings - Lawson, C; Mann, D; Lewis, O (2012)
We used manipulative field exclusion experiments to investigate the effects of dung beetles on the spatial aggregation of emerging seedlings of two tropical tree species. The results provide the first direct demonstration that tropical dung beetles reduce seedling clustering, with important implications for plant densities and demography. © 2012 by The Association for Tropical Biology and Conservation.